Cartilage tympanoplasty for retraction pocket of the tympanic membrane in children - Milan Urík; Kateřina Sobotková; Michal Bartoš; Josef Machač; Vít Kruntorád; Jiří Jarkovský (Frontiers Media S.A., 2024)
BackgroundRetraction pocket (RP) of the tympanic membrane (TM) is a common pathology in children that can cause ossicular chain erosion, cholesteatoma formation, and potentially life-threatening complications of cholesteatoma. This study assessed the functional and anatomical results of cartilage grafting in children with severe RP of the TM.MethodsThis was a retrospective review of 212 children from a tertiary referral center.ResultsWe identified significant differences in hearing results, indication criteria, and location of TM fixation between stages II and III of RP (according to Charachon). We observed a significantly higher incidence of RP in boys than in girls.ConclusionsCartilage tympanoplasty for retraction pocket of the tympanic membrane in children is a safe procedure with good anatomical and hearing results.